2021
DOI: 10.3390/ijms22115460
|View full text |Cite
|
Sign up to set email alerts
|

Possible Beneficial Actions of Caffeine in SARS-CoV-2

Abstract: The COVID-19 pandemic has established an unparalleled necessity to rapidly find effective treatments for the illness; unfortunately, no specific treatment has been found yet. As this is a new emerging chaotic situation, already existing drugs have been suggested to ameliorate the infection of SARS-CoV-2. The consumption of caffeine has been suggested primarily because it improves exercise performance, reduces fatigue, and increases wakefulness and awareness. Caffeine has been proven to be an effective anti-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 90 publications
0
17
0
3
Order By: Relevance
“…The lack of a clear trend in coffee consumption as the result of the COVID-19 pandemic calls for further investigation. Moreover, potential health implications should not be overlooked, especially since caffeine consumption may directly or indirectly promote bronchodilation, interfere in the process of immunomodulation, and hinder viral intracellular transcription while undergoing COVID-19 infection [33]. Furthermore, reflecting a discomfited mood and socially confining setting, we found a marked increase in tea consumption.…”
Section: Discussionmentioning
confidence: 75%
“…The lack of a clear trend in coffee consumption as the result of the COVID-19 pandemic calls for further investigation. Moreover, potential health implications should not be overlooked, especially since caffeine consumption may directly or indirectly promote bronchodilation, interfere in the process of immunomodulation, and hinder viral intracellular transcription while undergoing COVID-19 infection [33]. Furthermore, reflecting a discomfited mood and socially confining setting, we found a marked increase in tea consumption.…”
Section: Discussionmentioning
confidence: 75%
“…This methylxanthine showed a significant binding energy with ACE2 when complexed to the active site of protein S plus ribavirin (Mohammadi et al, 2020 ), it either had good binding affinity to Mpro (Elzupir, 2020 ) and RdRp (Abd El‐Aziz et al, 2021 ). A review of possible beneficial actions of caffeine for COVID‐19 concluded that caffeine can be favoring bronchodilatation, immunomodulation and probably hindering viral intracellular transcription (Romero‐Martínez et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Coffee and tea are important sources of dietary caffeine, a drug more commonly known for its psychostimulant effects. However, caffeine and its methylxanthine metabolites present with other potentially immunomodulatory properties [ 40 , 41 ]. Experimental studies of caffeine favor inhibitory effects on the proliferation of stimulated lymphocytes, activity of macrophages and natural killer cells, and levels of anti-inflammatory cytokines [ 40 ].…”
Section: Discussionmentioning
confidence: 99%